CATASTRE OF ENDOPARASITE FAUNA OF JUMBO FLYING SQUID DOSIDICUS GIGAS (CEPHALOPODA) IN THE NORTH OF PERU - Iannacone, Jose (2009)
Jumbo Flying Squid Dosidicus gigas (Orbigny 1835) is one of higher size of cephalopod and abundant in pelagicoceanic environment. This migratory specie and endemic from Southeast Pacific is a hydrobiological resource of hig economic importance in Peru. During 2008 and 2009 42 squid of dorsal mantle length between 53.5 cm and 93 cm, proceeding from Sechura (n= 22, 52.3%), Paita (n= 16, 38.1%), Chimbote (n= 2, 4.7%) and Bayovar (n= 2, 4.7%) were surveyed. Atotal of five larva helminths in mantle and muscular fibres with the following descriptors of parasite ecology were registered: principal Tentacularia coryphaenae Bosc, 1797 (Prevalence = 90.4%; Mean abundance = 3.97); secondary Anisakis physeteris Baylis, 1923 (Prevalence = 19.1%; Mean abundance = 0.33); rare Anisakis simplex (Dujardin, 1845) (Prevalence = 4.7%; Mean abundance = 0.07); rare Porrocaecum sp. (Prevalence = 2.3%; Mean abundance = 0.02); and rare Contracaecum sp. (Prevalence = 2.3%; Mean abundance = 0.02). An ausense of lineal relation with host DMLwas observed, and prevalence and mean abundance media of T. coryphaenae and global parasitism. Prevalence of A. physeteris not presented a lineal relation with host length. By chance unically, mean abundance of A. physeteris had a direct linear relation with DMLof D. gigas. Both species de Anisakis employ jumbo flyind squid as paratenic host (ciclogenic transport) and can produce anisakiosis (or anisakiasis), a zoonotic human parasitosis of digestive tract.